Inhibition of Sat1 alleviates myocardial ischemia-reperfusion injury through regulation of ferroptosis via MAPK/ERK pathway - Liu, Zhou; Chen, Hongjin; Song, Yingnan; Chen, Kaiyuan; Pan, Sisi; Yang, Siyuan; Lu, Deqin (Frontiers in Pharmacology, 2024)
Introduction Myocardial ischemia-reperfusion injury (MIRI) is a prevalent complication in patients with myocardial infarction. The pathological mechanism of MIRI remains elusive. Ferroptosis plays a critical role in MIRI. This study aimed to investigate the role of spermidine/spermine N1-acetyltransferase 1 (Sat1) in MIRI by regulation of ferroptosis. Methods Rats and H9C2 cells were used to perform MIRI model. The extent of myocardial damage and associated pathological changes were evaluated. Protein expression was detected by western blot. Then we observed the mitochondrial morphology and measured cell viability and damage. The levels of lipid peroxide and glutathione were measured, and lipid reactive oxygen species (ROS) was quantified. Differentially expressed genes (DEGs) in MIRI were analyzed. Moreover, to explore the role of Sat1 in MIRI, this study utilized adeno-associated virus 9 and lentiviral transduction to modulate Sat1 expression in rats and H9C2 cells, respectively. The transcription factor that regulates Sat1 expression was predicated. Luciferase reporter gene experiment was conducted to reveal the potential sites of Sox2 binding to Sat1. Results This study revealed that ferroptosis was involved in MIRI. Through bioinformatic analysis, Sat1 was identified as a significant gene in MIRI, which has been reported as an inducer of ferroptosis. Our results showed that Sat1 expression was significantly increased in MIRI. Next, the study showed that inhibition of Sat1 alleviated MIRI by suppressing ferroptosis in vivo and in vitro, and over-expression of Sat1 promoted MIRI via activation of ferroptosis. Furthermore, Sat1 and its interacting genes were enriched in several signaling pathways, including ferroptosis and the MAPK signaling pathway. The results showed that Sat1 regulated MIRI through ferroptosis via MAPK/ERK pathway. Moreover, it is found that Sox2 can suppress Sat1 expression at the transcriptional level. The potential binding site was TAACAAAGGAA. Conclusion In sum, this study demonstrated Sat1 expression was increased in MIRI, inhibition of Sat1 can alleviate MIRI by regulating ferroptosis via MAPK/ERK pathway, and Sat1 was negatively regulated by Sox2. These findings suggested that Sat1 may serve as a potential therapeutic target for the treatment of MIRI.